Modern concepts o f endometrial receptivity in endometriosis-associated infertility (analytical review) - I. M. Ordiyants; Z. V. Zyukina; D. S. Novginov; D. R. Asatryan (Фундаментальная и клиническая медицина, 2023)
Here we provide the recent information on the molecular profile of the endometrium and highlight the pathogenesis of infertility occurring during endometriosis. Because of individual features of each woman’s organism, there are no versatile diagnostic criteria for determining endometrial receptivity which plays one of the leading roles in implantation disorders. Although a lot of studies on the gene expression in endometriosis have been published to date, intricate gene-gene and gene-environment interactions frequently balance inherited or acquired alterations of gene expression in the endometrium. Hence, investigation of entire cell signaling pathways is preferrable over the general expression of gene expression within the endometrium. As eutopic and ectopic endometrium have largely similar histological appearance, the development of a single diagnostic test remains an unmet clinical need. Therefore, it is urgent to search for novel, evidence-based criteria for timely prediction and early diagnosis of endometriosis-associated infertility using minimally invasive examination methods.